2022
DOI: 10.1038/s41598-022-13463-z
|View full text |Cite
|
Sign up to set email alerts
|

N-oleoylethanolamide treatment of lymphoblasts deficient in Tafazzin improves cell growth and mitochondrial morphology and dynamics

Abstract: Barth syndrome (BTHS) is caused by mutations in the TAZ gene encoding the cardiolipin remodeling enzyme, Tafazzin. The study objective was to quantitatively examine growth characteristics and mitochondrial morphology of transformed lymphoblast cell lines derived from five patients with BTHS relative to five healthy controls, as well as the therapeutic potential of oleoylethanolamide (OEA) and linoleoylethanolamide (LEA). These bioactive lipids both activate PPARα, which may be therapeutic. BTHS lymphoblasts gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The organic phase was carefully collected and desiccated under a stream of nitrogen gas. To separate the individual phospholipid species, the organic phase was resuspended in chloroform and applied onto Silica Gel HF plates measuring 20 cm × 20 cm with a layer thickness of 250 μM (Analtech Inc., Cole-Parmer Canada, Montreal, QC, Canada), and resolved using thin-layer chromatography with a solvent system of chloroform:methanol:2-propanol:0.25% KCl:trimethylamine (30:9:25:6:18, v / v/v / v/v ) [ 26 ]. Cardiolipin bands were detected using UV illumination after spraying with 0.1% 2,7-dichlorofuorescin in methanol ( w / v ) and scrapped in reference to known cardiolipin standards (Avanti Polar Lipids, Millipore Sigma, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…The organic phase was carefully collected and desiccated under a stream of nitrogen gas. To separate the individual phospholipid species, the organic phase was resuspended in chloroform and applied onto Silica Gel HF plates measuring 20 cm × 20 cm with a layer thickness of 250 μM (Analtech Inc., Cole-Parmer Canada, Montreal, QC, Canada), and resolved using thin-layer chromatography with a solvent system of chloroform:methanol:2-propanol:0.25% KCl:trimethylamine (30:9:25:6:18, v / v/v / v/v ) [ 26 ]. Cardiolipin bands were detected using UV illumination after spraying with 0.1% 2,7-dichlorofuorescin in methanol ( w / v ) and scrapped in reference to known cardiolipin standards (Avanti Polar Lipids, Millipore Sigma, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, both studies provided new evidence to support that cardiolipin remodeling may not be required to improve mitochondrial function in this syndrome. One study 9 showed that N- oleoyl-ethanolamide treatment significantly improved mitochondrial morphology and function of BTHS lymphoblasts, possibly by affecting mitochondrial dynamics without resolving cardiolipin alterations. The other one 10 reported that SS-31 peptide improved mitochondrial respiratory capacity and promoted supercomplex organization in a BTHS animal model without affecting altered cardiolipin remodeling.…”
mentioning
confidence: 99%